دور الثقة التنظيمية في تعزيز الإبداع التنظيمي - حسين, حميد; وليد, داده; مصعب, سواكر (unuversity of eloued- جامعة الوادي, 2023)
"انطلقت الدراسة الحالية الموسومة بعنوان"" دور الثقة التنظيمية في تعزيز الإبداع التنظيمي في المؤسسة العمومية"" من إشكالية رئيسية وهي: هل هناك أثر للثقة التنظيمية في تعزيز الابداع التنظيمي لدى الموظفين في مؤسسة بلدية النخلة؟, وللإجابة على هذا السؤال تم تحديد الفرضية التالية: هناك أثر للثقة التنظيمية في تعزيز الابداع التنظيمي لدى الموظفين في مؤسسة بلدية النخلة. تهدف الدراسة إلى العمل على التعرف على للدور الذي تلعبه الثقة التنظيمية في تعزيز الابداع التنظيمي لدى الموظفين في مؤسسة محل الدراسة, حيث انها استخدمت المنهج الوصفي التحليلي كونه الذي يتناسب مع طبيعة البحث, تم اختيار العينة بطريقة عشوائية والتي تتكون من (40) موظف وموظفة في بلدية النخلة. النتائج التي توصلت إليها الدراسة: 1 يوجد دور للثقة التنظيمية التي تضعها المؤسسة في العاملين في تعزيز الابداع التنظيمي لدى الموظفين في مؤسسة بلدية النخلة . 2 يوجد دور للثقة بالزملاء في المؤسسة في تعزيز الإبداع التنظيمي لدى الموظفين في مؤسسة بلدية النخلة . 3 إن الثقة بالرئيس المباشر دورا في تعزيز الإبداع التنظيمي لدى الموظفين في مؤسسة بلدية النخلة . 4 إن للثقة بالإدارة العليا دورا كبيرا في تعزيز الإبداع التنظيمي لدى الموظفين في مؤسسة بلدية النخلة . " "The current study titled ""The Role of Organizational Trust in Promoting Organizational Creativity in the Public Institution"" started from a major problem, namely: Is there an effect of organizational confidence in enhancing organizational creativity among employees in the Palm Municipal Corporation? To answer this question, the following hypothesis was identified: There is an effect For organizational confidence in enhancing organizational creativity among employees of the Palm Municipal Corporation. The study aims to work on identifying the role that organizational trust plays in promoting organizational creativity among employees in the institution under study, as it used the descriptive analytical approach as it is commensurate with the nature of the research. The sample was chosen randomly, which consists of (40) employees in Palm municipality. The findings of the study: 1) There is a role for the organizational trust placed by the institution in the employees in enhancing the organizational creativity of the employees in the Palm Municipality Corporation. 2) There is a role for trusting colleagues in the institution in promoting organizational creativity among employees in the Palm Municipality Corporation. 3) Confidence in the line manager plays a role in enhancing the organizational creativity of employees in the Palm Municipal Corporation. 4) Confidence in senior management has a major role in enhancing the organizational creativity of employees in the Palm Municipal Corporation. "
Keywords: الثقة التنظيمية - الإبداع التنظيمي – التحفيز- زيادة الانتاجية - الميزة التنافسية - القدرة الإنتاجية - القيادة الناجحة - -الإستراتيجية - الفكر التنظيمي - الثقافة التنظيمية .; Confiance organisationnelle - créativité organisationnelle - motivation - productivité accrue - avantage concurrentiel - capacité productive - leadership réussi - stratégie - pensée organisationnelle - culture organisationnelle .